2009
DOI: 10.1104/pp.108.134353
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary History and Stress Regulation of Plant Receptor-Like Kinase/Pelle Genes    

Abstract: Receptor-Like Kinase (RLK)/Pelle genes play roles ranging from growth regulation to defense response, and the dramatic expansion of this family has been postulated to be crucial for plant-specific adaptations. Despite this, little is known about the history of or the factors that contributed to the dramatic expansion of this gene family. In this study, we show that expansion coincided with the establishment of land plants and that RLK/Pelle subfamilies were established early in land plant evolution. The RLK/Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
426
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 351 publications
(448 citation statements)
references
References 104 publications
10
426
2
2
Order By: Relevance
“…However, SNPs within Sb03g006765 at position 7 Mb are not in LD with those within the SbPSTOL1 cluster at position 60 Mb, suggesting that multiple SbPSTOL1 homologs enhance sorghum performance under low-P conditions, likely by the same overall physiological mechanism based on root morphology modulation. Lehti-Shiu et al (2009) found that RLKs present in tandem repeats were more likely than nontandem RLKs to be up-regulated by biotic stress factors and UV-B light in Arabidopsis, suggesting that the SbPSTOL1 homologs close together at position 60 Mb on chromosome 3 may constitute a functional module controlled by common regulatory elements. If so, similar to the case for maize aluminum tolerance (Maron et al, 2013), tandem duplication events may provide an additional level of regulation, leading to enhanced gene expression and increased P acquisition controlled by PSTOL1 homologs in sorghum.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, SNPs within Sb03g006765 at position 7 Mb are not in LD with those within the SbPSTOL1 cluster at position 60 Mb, suggesting that multiple SbPSTOL1 homologs enhance sorghum performance under low-P conditions, likely by the same overall physiological mechanism based on root morphology modulation. Lehti-Shiu et al (2009) found that RLKs present in tandem repeats were more likely than nontandem RLKs to be up-regulated by biotic stress factors and UV-B light in Arabidopsis, suggesting that the SbPSTOL1 homologs close together at position 60 Mb on chromosome 3 may constitute a functional module controlled by common regulatory elements. If so, similar to the case for maize aluminum tolerance (Maron et al, 2013), tandem duplication events may provide an additional level of regulation, leading to enhanced gene expression and increased P acquisition controlled by PSTOL1 homologs in sorghum.…”
Section: Discussionmentioning
confidence: 99%
“…Although RLKs have been found to be important regulators of root hair growth in Arabidopsis under low-P conditions (Lan et al, 2013), their role seems to be much more general, as they also function in defense and stress responses, including drought, salinity, and cold (Lehti-Shiu et al, 2009;Ye et al, 2009;Das and Pandey, 2010;Marshall et al, 2012;Schulz et al, 2013;Vivek et al, 2013), possibly acting as hubs in stress signaling and development (Das and Pandey, 2010;Asano et al, 2012;Schulz et al, 2013). Several RLKs such as CRPK1 have been shown to play key roles in abiotic stress tolerance, positively or negatively regulating stress tolerance by modulating abscisic acid signaling and reducing the accumulation of reactive oxygen species (Lan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8D). CRK expression has been shown to be modulated in response to ROS-and cellular redox state-related stresses (Lehti-Shiu et al, 2009;Wrzaczek et al, 2010;Bourdais et al, 2015). Moreover, CRKs are thought to be involved in cellular redox and apoplastic ROS sensing by the presence of conserved Cys residues in their apoplastic domain.…”
Section: The Apoplastic Redox State Influences Cellular Metabolismmentioning
confidence: 99%